Integrasi Metode Quiz Team dengan Talking Stick Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar - Ning Mukaromah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
This research aims to integrate the quiz team and talking stick methods, and see student responses to the implementation of these two methods. The research method uses a qualitative approach with a descriptive type. Data collection techniques using observation, surveys and interviews. The data source is the fifth grade PAI teacher at SDI Nurul Mushthofa Tambak Lekok and 19 fifth grade students. The results of this research are the implementation of the integration of the quiz team method with talking stick in PAI subjects at SDI Nurul Mushthofa Tambaklekok, namely planning/preparation, implementation (introduction, core and closing activities) and evaluation. 19 students' responses stated that PAI teachers implemented integration of 2 methods, 17 students were happy and 2 people were not happy. 17 students expressed increased motivation to learn, 2 students stated they were less motivated. 17 students found it easier to understand the material, and 2 said it was difficult for them to understand the lesson material. 16 students had the courage to express their opinion in class, 3 people were not confident to express their opinion in front of the class. And 17 students said they were active and 2 students or 11% said they were not active.